Third Five Year Plan (A Draft Outline) Government of Gujarat - Planning Commission (Planning Commission, 1960)
The state of Gujarat came into existence on the 1st of May, 1960, as a result of the Bombay Re-organisation Act 1960. There exist large areas in the state which are comparatively underdeveloped. At the same time there are immense untapped resources which can be profitably exploited For a proper appreciation of the Third Five Year Plan and the directions in which future development is visualised, it is necessary, therefore, to have a brief idea of the physical and economic features of the state.
General Administration Department (Planning), Government of Gujarat